Determinan Kesehatan Ibu Hamil Tentang Tanda Bahaya Kehamilan dengan Pencapaian Kontak Minimal 4 Kali Selama Masa Kehamilan (K4) - Katmini Katmini (Poltekkes Kemenkes Surakarta, 2020)
Background: Danger sign of pregnancy was a sign that someone who pregnant have a serious problem with the mother or fetus. Contact at least 4 times during pregnancy (K4) was the fourth contact of pregnant women with the medical employee (or more), to obtain antenatal care according to established standards, provided that at least one contact in the first trimester, one contact on the second trimester and two contact times in the third trimester. The purpose of this study was to determine the correlation between knowledge pregnant women about the danger signs of pregnancy with the achievement of K4.Methods: The research method was using analytical research design type of cross sectional correlation. The subjects in this study was the entire third trimester pregnant women in the Selopanggung Village Semen District Regency of Kediri as many as 12 people, sampling technique using saturation sampling and research in March until April 2019. Measuring instrument used was questionnaire and book KIA. Data analysis was using Fisher Probability Exact Test. Results: The results showed all third trimester pregnant women have a good knowledge (100%) and as much as 33% of pregnant women can achieve K4. The analysis showed that the calculated p value was 1 greater than 0.01 so there wasn’t correlation between knowledge pregnant women about the danger signs of pregnancy with the achievement of K4. Conclusion: This research was expected to increase further-enhance-the-achievement-of-K4 by medical employee with_home_visit.